Educational unmanned surface robot - Chua, Zong You (2015)
This report serves to discuss and document the process on building a learning platform for student. The purpose is to inspire and cultivate students’ interest in programming. The report will give insight of two different commonly explored programming languages that is C and Java Language. Explanations and illustrations will be provided on how programs can interact with the learning platform. The overall approach is to create an Educational Unmanned Surface Robot as a learning platform. Upon completion of this Educational Unmanned Surface Robot, together with creativity, students will escalate appreciation on the vast potential of programming in reality application especially in the info-communication era.